2018
DOI: 10.31025/2611-4135/2018.13663
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fine Fractions From Landfill Mining: A Review of Previous Investigations

Abstract: Several landfill mining (LFM) studies have been carried out in recent years all around the world. From these studies qualitative and quantitative information regarding the composition and characteristics of the different fractions excavated from landfills has been obtained. This information comprises data from various landfill sites around the globe from which useful correlations for future LFM projects can be identified. Of particular interest to this paper is the information regarding the fine fractions, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 57 publications
(160 reference statements)
2
29
0
Order By: Relevance
“…Significant moisture and organic matter contents are normally to be expected in the fine fractions. These interrelated parameters are of critical relevance, since processing routes and possible end uses for these fractions will depend on their quantities (Parrodi et al, 2017). The moisture content and organic content in finer fraction of MSW were found to be least at the Kadapa site, while at the Hyderabad landfill these were found to be higher.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant moisture and organic matter contents are normally to be expected in the fine fractions. These interrelated parameters are of critical relevance, since processing routes and possible end uses for these fractions will depend on their quantities (Parrodi et al, 2017). The moisture content and organic content in finer fraction of MSW were found to be least at the Kadapa site, while at the Hyderabad landfill these were found to be higher.…”
Section: Resultsmentioning
confidence: 99%
“…The high soil-like content in the aged MSW is likely the result of daily covering soil, street sweepings, drain silt and construction and demolition (C&D) waste along with the humification of organic matter in the fresh MSW (Parrodi et al, 2017). Several definitions for 'finer fractions' are available in the literature depending upon the sieve size adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Typical recoverable materials are metals, plastic and other combustibles, and mineral materials (stones, glass). One of the main barriers to landfill mining is the lack of use of the fine fraction [60,67,68].…”
Section: Biocoversmentioning
confidence: 99%
“…Owing to their similarities with natural soil, many previous studies indicated this fine material as "soil-like" fraction (e.g., Abreu & Vilar, 2017;Cheng-liang et al, 2016;Mohit, Manoj, Ramana, & Sreekrishnan, 2018;Quaghebeur et al, 2013). The high soil-like content in the aged MSW is likely the result of daily covering soil, street sweepings, drain silt, and construction and demolition waste along with the humification of organic matter in the fresh MSW (Parrodi, Hollen, & Pomberger, 2017). Notably, Humus is the stable state reached by organic matter after being degraded down to the point where organic matter resists further degradation and constitutes one of the main components of soil, together with liquid, gases, minerals and living microorganisms (Stevenson, 1994).…”
Section: Core Ideasmentioning
confidence: 98%